2002
DOI: 10.1093/aje/155.10.958
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Symptom Domains in Otitis Media: A Longitudinal Study of 1,373 Twin Pairs

Abstract: Research on risk factors and pathogenesis of otitis media has emphasized the environment, but previous twin studies suggest a strong genetic component. In those studies, no attempt was made to differentiate the role of initial acute infection from the chronic airway blockage that frequently accompanies persistent effusion. The authors estimated genetic and environmental determination of both of these aspects of otitis media histories at three time points. A large and representative subset of a total population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 28 publications
(32 reference statements)
8
57
2
1
Order By: Relevance
“…The first family study of COME/ROM (Daly et al 1996) demonstrated that first-degree relatives (parents and siblings) of probands with COME/ROM had greater than expected rates of OM based on population rates. Subsequent twin and triplet studies confirmed the strong familial aggregation of COME and ROM, with heritability estimates of 0.64-0.74 in monozygotic twins and 0.20-0.53 in dizygotic twins (Kvaerner et al 1997;Casselbrant et al 1999;Rovers et al 2002;Kvestad et al 2004Kvestad et al , 2006. Two linkage studies for COME/ROM have been published to date (Daly et al 2004;Casselbrant et al 2009;Chen et al 2011); however, the loci identified in the two studies did not overlap.…”
Section: Introductionmentioning
confidence: 95%
“…The first family study of COME/ROM (Daly et al 1996) demonstrated that first-degree relatives (parents and siblings) of probands with COME/ROM had greater than expected rates of OM based on population rates. Subsequent twin and triplet studies confirmed the strong familial aggregation of COME and ROM, with heritability estimates of 0.64-0.74 in monozygotic twins and 0.20-0.53 in dizygotic twins (Kvaerner et al 1997;Casselbrant et al 1999;Rovers et al 2002;Kvestad et al 2004Kvestad et al , 2006. Two linkage studies for COME/ROM have been published to date (Daly et al 2004;Casselbrant et al 2009;Chen et al 2011); however, the loci identified in the two studies did not overlap.…”
Section: Introductionmentioning
confidence: 95%
“…5 A longitudinal study reported that the heritability of symptom scores, composed of ear infection and respiratory symptoms, increased with age, from 0.49 at age 2 to 0.71 at age 4 (see ref. 6). These studies confirm a substantial heritable component to the broad clinical spectrum of OM.…”
Section: Introductionmentioning
confidence: 99%
“…9 The influence of genetically determined variations on otitis media can be illustrated by twin studies, which have shown a heritability of 57% for acute ear infections and 72% for chronic ear infections. [10][11][12][13][14] Correlation for recurrent otitis media is higher in monozygotic twins (65%-71%) compared with dizygotic twins (25%-34%). 15 Streptococcus pneumoniae is an important pathogen in otitis media and is involved in at least 20% to 40% of all cases.…”
mentioning
confidence: 99%